Empathy and the other: difference, connection, and the teaching of writing - Blankenship, Lisa, editor; Leake, Eric, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2026)
sing reflective approaches to empathy, this collection teaches students and teachers how to be with others in ways that provide hope for our collective futures by using empathy as a way to mitigate despair at the state of the world and as a way of being and relating to others.--Provided by publisher.
Empathy and the teaching of writing: an introduction and overview / Lisa Blankenship and Eric Leake -- Un-disciplining writing: an education in empathy for writing instruction / Harry Thorne and Rosanne Carlo -- Feeling with writing assessment: empathy, antiracism, and disciplinary infrastructure / J. W. Hammond -- What can we learn about empathy from design thinking theory and practice? / Scott Wible -- Resonant reflection: cultivating empathetic dispositions in writing centers / Mitch Hobza -- Empathy exchange: connecting to audience through narrative, listening, and regard for the other / Renea Frey -- Building empathy through embodied, place-based learning: engaging difference in students' civic experiences / Ashley J. Holmes -- African restorative justice and the composition classroom / Nadya Pittendrigh and Saidat Ilo -- Necessary context: In the dream house and the politics of citation / Theresa A. Kulbaga -- Reconsidering Rogerian empathic understanding in the twenty-first century / Nathaniel Teich -- A pedagogy of racial reflexivity, or, Critiquing the roles of the empathetic ally / Dylan Marie Colvin and Eric A. House.
Keywords: English language -- Rhetoric -- Study and teaching; Empathy -- Study and teaching (Higher); Social justice and education